Ulon Coffee Shop's Web-Based Raw Material Stock Management Information System Using the Just-In-Time Method - Pajar, Rahmat; Kusnadi , Kusnadi; Suwandi , Suwandi (Jurnal Info Sains : Informatika dan Sains, 2025)
Raw material stock management is an important aspect in the smooth operation of the Food and Beverage (F&B) business. Coffee Shop Ulon, which operates in the coffee beverage sector, still records stock manually, which often causes problems such as the accumulation of materials with a short shelf life or stock shortages that impact service. To overcome this, an information system is needed that is able to manage inventory more efficiently, accurately, and integrated. This study aims to build a Web-Based Raw Material Stock Management Information System Using the Just In Time (JIT) Method with the PHP (Laravel) programming language and MySQL as a database. The implementation of the JIT method is expected to help Coffee Shop Ulon ensure the availability of raw materials according to needs, reduce waste due to expired materials, and prevent stock shortages. The results of this study are a web-based information system with features for recording incoming and outgoing raw materials, expiration reports (waste), minimum stock reminders, and recording supplies from suppliers. With this system, stock management at Coffee Shop Ulon becomes more organized, efficient, and supports fast and accurate decision making.